THE ROLE OF SOCIAL MEDIA IN CUSTOMER PURCHASE DECISIONS THROUGH MARKETING MANAGEMENT AMONG TIKTOK SHOP USERS IN INDONESIA (2025) - Irfan , Irfan (Universitas muhammadiyah malang, 2025)
This study aims to describe the condition of social media, marketing management, and purchase decision, analyze the influence of social media on purchase decision, analyze the influence of social media on marketing management, analyze the influence of marketing management on purchase decision, and analyze the role of marketing management in mediating the influence of social media on purchase decision. The population in this study were TikTok Shop users in Indonesia with a total of 50 respondents selected using purposive sampling technique. The method used was the Process Macro Hayes with SPSS 25. The results of this study indicate that social media has a significant positive effect on purchase decision, social media has a significant positive effect on marketing management, marketing management has a significant positive effect on purchase decision, and marketing management can mediate the influence of social media on purchase decision.